2012
DOI: 10.1158/1078-0432.ccr-12-0060
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chemotherapy on Cognitive Function in a Mouse Model: A Prospective Study

Abstract: Purpose: Clinical studies indicate that up to 70% of patients with cancer who receive chemotherapy experience cognitive impairment. The present study used a prospective longitudinal design to assess short-and long-term effects of commonly used anticancer drugs on cognitive performance in a mouse model.Experimental Design: Normal mice received three weekly injections of a combination of methotrexate þ 5-fluorouracil (CHEMO group) or an equal volume of saline (SAL group). Cognitive tests, measuring different asp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 35 publications
6
27
1
Order By: Relevance
“…Taken together, these findings suggest that agonists of nAChRs may be therapeutic to those suffering from 'chemo-brain. ' Many aspects of cognitive function can be assessed in animals using well established behavioral procedures, and studies have demonstrated the presence of cognitive deficits in animals following exposure to chemotherapeutic agents using several behavioral tasks [74][75][76]. Animals exposed to chemotherapeutic agents exhibit deficits in tests of attention and working memory, recognition memory, associative learning and memory and spatial memory [77], in agreement with clinical observations of 'chemo-brain.'…”
Section: Cognition and The Cholinergic Systemsupporting
confidence: 53%
See 1 more Smart Citation
“…Taken together, these findings suggest that agonists of nAChRs may be therapeutic to those suffering from 'chemo-brain. ' Many aspects of cognitive function can be assessed in animals using well established behavioral procedures, and studies have demonstrated the presence of cognitive deficits in animals following exposure to chemotherapeutic agents using several behavioral tasks [74][75][76]. Animals exposed to chemotherapeutic agents exhibit deficits in tests of attention and working memory, recognition memory, associative learning and memory and spatial memory [77], in agreement with clinical observations of 'chemo-brain.'…”
Section: Cognition and The Cholinergic Systemsupporting
confidence: 53%
“…Tasks involving serial search sequences such as the radial arm maze or requiring the use of information from an immediately preceding trial such as the nonmatching to sample or delayed non-matching to sample task are frequently used to assess working memory function. During training in the submerged radial arm maze, rats receiving a single exposure to the chemotherapeutic agent carmustine exhibit an increased number of errors when compared to controls, indicative of impaired working memory [93], and exposure to the chemotherapeutic combination methotrexate and 5-fluorouracil has been shown to impair performance on non-matching to sample and delayed non-matching to sample tasks [66, 76,94].…”
Section: Attention and Working Memorymentioning
confidence: 99%
“…Exposure to chemotherapeutic agents was associated with decreased performance on different types of learning tasks utilizing hippocampal and frontal network functions [17][18][19][20].…”
Section: Manymentioning
confidence: 99%
“…To date, measures of chemotherapy-induced cognitive deficits in rodents have predominantly focused on hippocampal and frontal dependent functions including spatial navigation (Morris Water maze), novelty recognition (novel location recognition), associative learning and memory (non-match to sample and delayed non-match to sample). Chemotherapy impaired spatial memory, conditional associative learning, and discrimination learning (some of which were chronically observed (Winocur, Henkelman, Wojtowicz, Zhang, Binns, and Tannock, 2012)), and it suppressed hippocampal neurogenesis (Winocur et al, 2015). …”
Section: Introductionmentioning
confidence: 99%